Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Goal‐oriented adaptivity based on a model hierarchy of mean‐field and full‐field homogenization methods in elasto‐plasticity - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Transferability of a discrepancy model for the dynamics of electromagnetic oscillating circuits - Wohlleben, Meike Claudia; Muth, Lars; Peitz, Sebastian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics)
Modelling of dynamic systems plays an important role in many engineering disciplines. Two different approaches are physical modelling and data‐driven modelling, both of which have their respective advantages and disadvantages. By combining these two approaches, hybrid models can be created in which the respective disadvantages are mitigated, with discrepancy models being a particular subclass. Here, the basic system behaviour is described physically, that is, in the form of differential equations. Inaccuracies resulting from insufficient modelling or numerics lead to a discrepancy between the measurements and the model, which can be compensated by a data‐driven error correction term. Since discrepancy methods still require a large amount of measurement data, this paper investigates the extent to which a single discrepancy model can be trained for a physical model with additional parameter dependencies without the need for retraining. As an example, a damped electromagnetic oscillating circuit is used. The physical model is realised by a differential equation describing the electric current, considering only inductance and capacitance; dissipation due to resistance is neglected. This creates a discrepancy between measurement and model, which is corrected by a data‐driven model. In the experiments, the inductance and the capacity are varied. It is found that the same data‐driven model can only be used if additional parametric dependencies in the data‐driven term are considered as well.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics